Effect of fluorination on the lanthanum-doped AB(2)-type metal hydride electrodes - Park, HY; Cho, WI; Cho, BW; Lee, SR; Yun, KS (ELSEVIER SCIENCE SA, 2001)
The effect of fluorination on the surface of an AB(2)-type hydrogen-storage alloy with the composition Zr0.7Ti0.3V0.4Mn0.4Ni1.2 is investigated. Electron probe microanalysis (EPMA), scanning electron microscopy (SEM), Anger electron spectroscopy (AES), and X-ray diffraction (XRD) techniques show that the fluorinated AB(2)-type alloys have a unique surface morphology and high reactivity with a protective film. The treatment is found to be effective when lanthanum is incorporated in the alloy. The cycle-life of the metal hydride (MH) electrode increases significantly as a result of a decrease in the overpotential by electrode polarization. The degradation rate of the MH electrode is less than 3% after 100 cycles when lanthanum is added at 1-3 wt.%. (C) 2001 Elsevier Science B.V. All rights reserved.
Keywords: ACTIVE SURFACE; LANI5; ALLOYS